Risk Exposure and Acquisition of Macroeconomic Information - Christopher Roth; Sonja Settele; Johannes Wohlfart (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We conduct an experiment with a representative sample from the US to study households' demand for macroeconomic information. Respondents who learn of a higher personal exposure to unemployment risk during recessions increase their demand for an expert forecast about the likelihood of a recession. Our findings are consistent with the basic premise of theories of rational inattention that demand for information depends on its expected benefit. Moreover, the fact that perceived risk exposure responds to information highlights frictions in households' knowledge about the personal relevance of particular pieces of information. Our findings inform the modeling of information frictions in macroeconomics.
Keywords: D12; D14; D83; D84; E32; G11; 330; risk exposure; macroeconomic conditions; information acquisition; experiment